Exploration Of Matematical Concep And Natural Sciences From The Local Wisdom Of Society As Learning Materials In The Curriculum 2013 - Marianus, Marianus; Damaris, Damaris (Journal of Educational Method and Technology, 2018)
The population growth is closely related to the utilization of natural resources and will impact on environmental degradation. Therefore, identifying and inventorying the local wisdom of the community that aims to conserve the environment is very important. Natural science perspective lifting local wisdom in education is one way to revitalize, develop and maintain the values of local knowledge. This study aims to explore the elements of local wisdom in society, examines the concept of Natural Science and Mathematics contained in the elements of local wisdom and is designed for learning materials. The research was conducted in the District Manganitu Sangihe Islands in January 2016. Data collection using observation techniques and interviews with related parties and data obtained analyzed the concept of science underlying the forms of local wisdom existing in Manganitu community.The result of the research is a concept map which contains the network of Mathematics and Natural Science concepts. This research product can meet the needs of high school teachers and become one of the solution of thematic learning problem in Sangihe Island.Keywords : Concept of Mathematics and Science, Local Community Wisdom, Curriculum 2013